Design and Implementation of Stepper 28BYJ-48 and Servo MG996R as a Roasting Arm Robot in an Arduino Uno-based Automatic Satay Grill Tool - Angga Muhammad Satria Nugroho; Rahmat Hidayat; Arnisa Stefanie (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2022)
Almost all factories use an automation system because the results are the fastest and better quality. Of course, these are the main factors in utilizing this automation system. However, in-home industries such as satay stalls, it is rare to find this automation technology. So we need a tool that is capable of baking the satay automatically. The solution was obtained by creating a roasting arm robot capable of engineering the satay roasting process based on the 28BYJ-48 stepper motor mechanism and the MG996R servo motor with Arduino UNO based control. This research is qualitative, quantitative experimental research fan. Data were collected by direct observation of the tools and interviews with satay traders. The results show that the roasting arm robot can carry out its duties optimally.